Ideological Shifts in Representing Gemblak: A Faircloughian Critical Discourse Analysis of Media and Fictional Texts - Rahmawati, Ida Yeni; Santoso, Anang; Syahri, Moch.; Cahyawati, Rina Susi; Ritenour, Makenna (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
Ideological change in the representation of gemblak is an important issue in social discourse studies. This research uses Fairclough's Critical Discourse Analysis (CDA) to examine the representation of gemblak in mass media and the novel Gemblak: Tragedi Cinta Budak Homoseks by Enang Rokajat Asura. The research objective is to reveal the language and ideology that shape the image of gemblak. The method used is qualitative with a discourse analysis approach. Data in the form of words, phrases, clauses, and sentences were collected through interviews and document studies. The results show that Detik News portrays gemblak positively as a figure who deserves respect, teaches politeness, and is good at socializing. In contrast, the novel frames gemblak as a negative figure, leading to bad judgment from society. This difference reflects the dynamics of power and changing social values in shaping the meaning of gem-blak. In conclusion, mass media and fiction have different ideological constructions in representing gemblak in the public sphere.